To Investigate the Effect of Heat Treatment on Low Carbon Steel Corrosion Behavior - Wahab Abdalrhem, Azhar; Jaber Naeemah, Ali; Noori jawad, Makki (International Journal of Engineering and Technology, 2018)
This work was to investigating the corrosion behavior of low carbon steel in a salt solution of 3.5wt% NaCl after undergoing two different types of heat treatment at 960 ºC in a furnace. The material of low carbon steel was cut into nine small pieces under three groups A, B and C, without heated annealing and hardening heat treatment respectively. The heat treatment was at temperature 960ºC. The hardness of the sample as received will be 203 kg/mm2 while after hardening the hardness was increased. The sample was mounted using hot and cold mounting. The microstructure and surface morphology was observed by using Scanning Electron Microscope (SEM) and Optical Microscope (OM) after grinding, polishing and etching on the sample. In group A cementite can be observed clearly on pearlite on the surface before corrosion test. After four days soaking in 3.5 wt% NaCl solution was observed all cementite and pearlite will be transformed to austenite with the remnants of cementite make the surface unstable hence increases the initial corrosion. After four days soaking when the cementite is oxidized and a thick film of corrosion product covers the material surface. The formation of Martensite due to quenching and rapid cooling in group C sample increases the corrosion rate from 0.072 mpy to 0.302 due to decreased of corrosion potential from -572 mV to -639 mV after four days soaking. The corrosion rate of each sample was measured by using electrochemical polarization measurement and Tafel extrapolation technique. From previous result, it was observed that samples which had undergone annealing mode of heat treatment turned out to be the ones with the best corrosion resistance.
Keywords: Cloud computing Infrastructure as a service (IaaS) Platform as a service (PaaS) Software as a Service (SaaS)